How Anode Porosity a ects the performance of a Solid Oxide Fuel Cell - Billemar, Jakob (My University, 2014)
The purpose of this project was to investigate how parameters, such as size of zirconia particles and the porosity, impact the performance of the anode of a solid oxide fuel cell. The analysis that has been conducted was focused on investigating SEM-pictures and analysing electrochemical impedance spec- troscopy(EIS) measurements on half-cells. The data suggest that an increasing porosity lead to an almost linear increase of TPBs/area in the range of 20- 40%. From the results, it was not obvious that the amount of triple phase boundaries(TPBs) was dependent on the size of the zirconia particles in the range between 0.12 and 1m. The EIS measurements suggest that the activation energy resulting from the first arc decreased as more measurements were done, at least for the sam- ple named Red. half-cell. This effect could be within the margin of errors, and hence just a coincidence. It could also be seen that the sample with the thickest electrolyte gave rise to the highest impedance, but not a much higher activation energy than the other reduced samples. Furthermore there appear to be a difference in shape between reduced and not reduced samples, and a substantial differences regarding activation energy and conductivity could also be seen.
Keywords: Nanoteknik; Grundläggande vetenskaper; Hållbar utveckling; Energi; Innovation och entreprenörskap (nyttiggörande); Nano Technology; Basic Sciences; Sustainable Development; Energy; Innovation & Entrepreneurship